Emotional Arousal Substrate in Relation to Eysenck Theory of Extraversion - Yusoff, Nasir; NurAzhani Anuar, Nik; Nor Arifin, Wan; Begum, Tahamina; Reza, Faruque (International Journal of Engineering and Technology, 2018)
Background: Eysenck theory posits that extraverts possess a trait of personality that is associated with personal enjoyment. Objectives: This study aims to examine the combination effect of extraversion and arousal intensity on the neural process of emotional arousal. Methods: This study was implemented in two parts â€“ (1) Validation of Extraversion-Five Factor Non Verbal Personality Questionnaire (E-FF-NPQ) for personality screening, and (2) Event Related Potential (ERP)/electroencephalograph (EEG) recording session. In part one, the E-FF-NPQ was validated by 153 respondents, recruited from Universiti Sains Malaysia. In part two, after having their personality trait screened, electroencephalogram was recorded in 90 participants (N=30 for each personality) during the Event Related Potential session. Emotional arousal pictures that were taken randomly from the International Affective Picture System (IAPS) were used as visual stimuli and divided into three categories (high, moderate, low) based on the normative mean values of IAPS. Results: Interaction effect of the extraversion trait and emotional arousal intensity was detected in the frontal region as indicated by the latency of N200. Conclusion: The Theory of Eysenck on the connection between extraversion and well-being is almost supported.Â Â